Superhydrophobic and superoleophobic property enhancement on guard ring micro-patterned PDMS with simple flame treatment. (1st March 2021) - Atthi, Nithi; Sripumkhai, Witsaroot; Pattamang, Pattaraluck; Thongsook, Oraphan; Meananeatra, Rattanawan; Saengdee, Pawasuth; Ranron, Norabadee; Pankong, Krynnaras; Uahchinkul, Warinrampai; Radomyos, Suphichaya; Srihapat, Arckom; Supadech, Jakrapong; et al.
Abstract: Effects of new micro-structure design, a flame treatment process, and the addition of semifluorinated silane (SFS) on an improvement of superhydrophobicity and superoleophobicity of PDMS surfaces were investigated in this study. PDMS and PDMS-SFS surfaces with the special design of circular rings and eight stripe supporters (C-RESS) with a hexagonal guard ring (HGR) structure were found to be the most durable which maintained their superhydrophobicity after scratch tests. The flame treatment at 700 °C/15 s formed a unique nanoscale flower-like on the PDMS-SFS surface. A formation of re-entrant micro-structure on the C-RESS with the HGR structure exhibited superhydrophobicity and superoleophobicity with water and ethylene glycol contact angles of 160.5° ± 2.0° and 160.2° ± 6.6°, respectively. The addition of the SFS was found to increase surface roughness and decrease surface energy. In conclusion, the flame-treated C-RESS with the HGR structure on the PDMS-SFS surface is considered one of the promising antifouling approaches in several applications.